Reducing Changeover Time Between Surgeries Through Lean Thinking: An Action Research Project - Amati, Mirjam; Valnegri, Alan; Bressan, Alessandro; La Regina, Davide; Tassone, Claudio; Lo Piccolo, Antonio; Mongelli, Francesco; Saporito, Andrea (Frontiers in Medicine, 2022)
Background Maximizing the utilization of the operating room suite by safely and efficiently changing over patients is an opportunity to deliver more value to patients and be more efficient in the oper-ating suite. Lean Thinking is a concept that focuses on the waste inadvertently generated during organization and development of an activity, which should maximize customer value while mini-mizing waste. It has been widely applied to increase process efficiency and foster continuous im-provement in healthcare and in the operating room environment. The objective of this paper is to provide insight on how healthcare professionals can be engaged in continuous improvement by embracing Lean Thinking and ultimately reducing changeover time between surgeries. Methods Using an action research approach, Lean methodology such as Gemba walks, Process Map-ping, Root-Cause-Analysis and the Single Minute Exchange of Dies (SMED) system was applied to understand the causes of variability and wastes concerning changeovers and improve processes in the context of gynecological- and general surgery. Data were collected and analyzed through observations and video recordings. Problem and issue have been raised to management team at-tention and included in the annual balanced scorecard of the hospital. This initiative has been also made relevant to the team working in the operating suite and related processes before and after the entry of the patient in the operating suite. Results Improved patient flow and inter-professional collaboration through standardized and safer work enabled effective parallel processing and allowed the hospital to reduce changeover time between operations by 25% on average, without changes in terms of infrastructure, technology or resources. Conclusion Lean thinking allowed the team to re-evaluate how the whole operating suite performs as a system, by starting from a sub-process as changeover. It is fundamental in order to improve fur-ther and obtain sustainable results over time, to act on a system level by defining a common goal between all stakeholders supported by a management and leading system such as visual/weekly management, optimizing planning, implementing standard-works to be followed by every associ-ate and guaranteeing the role of the surgeon as process driver who pull performances.